Human resource management practices and policies and employee organizational commitment in Bosnia and Herzegovina companies - Isada Mahmutović; Adisa Delić (Economic Review: Journal of Economics and Business, 2022)
Nowadays, when operating in an unstable market, organizations in Bosnia and Herzegovina (BiH) are also facing a continuous outflow of qualified employees to the countries of the European Union. In order to properly respond to the challenges from the environment, the organizations in BiH are forced to take adequate measures so as to become competitive in the market, which may prove to be difficult if they do not retain skilled workforce. This paper attempts to show that by implementing appropriate human resource management (HRM) practices and policies, organizations in BiH can affect employee organizational commitment, which will result not only in market survival but also in increased competitiveness, as the experience of the organizations in the surrounding countries shows that human resources is what gives these companies a competitive advantage. The paper aimed at examining the impact of characteristics, organizational characteristics, and HRM practices focused on performance appraisal, job security, employee participation, and career planning on employee organizational commitment in BiH companies with more than 50 employees in four sectors. The empirical research was conducted on a sample of 128 companies. The results show that when it comes to employee organizational commitment, HRM practices and policies bear more importance than demographic and organizational characteristics and that there is a statistically significant positive impact of HRM practices and policies on employee organizational commitment.
Keywords: L20; M54; 330; human resource management practices and policies; demographic and organizational characteristics; organizational commitment